2007
DOI: 10.1634/stemcells.2007-0293
|View full text |Cite
|
Sign up to set email alerts
|

c-Myb Is Required for Neural Progenitor Cell Proliferation and Maintenance of the Neural Stem Cell Niche in Adult Brain

Abstract: Ongoing production of neurons in adult brain is restricted to specialized neurogenic niches. Deregulated expression of genes controlling homeostasis of neural progenitor cell division and/or their microenvironment underpins a spectrum of brain pathologies. Using conditional gene deletion, we show that the proto-oncogene c-myb regulates neural progenitor cell proliferation and maintains ependymal cell integrity in mice. These two cellular compartments constitute the neurogenic niche in the adult brain. Brains d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
68
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 54 publications
3
68
0
1
Order By: Relevance
“…Foxj1 and c-Myb are known to be key transcription factors controlling RGC differentiation towards the ependymal cell lineage (Jacquet et al, 2009;Malaterre et al, 2008). To gain insight into the molecular pathway by which Mcidas and GemC1 regulate ependymal cell generation we examined the expression of Foxj1 and c-Myb following deletion or overexpression of Mcidas and GemC1.…”
Section: Mcidas and Gemc1 Promote The Generation Of Ependymal Cells Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Foxj1 and c-Myb are known to be key transcription factors controlling RGC differentiation towards the ependymal cell lineage (Jacquet et al, 2009;Malaterre et al, 2008). To gain insight into the molecular pathway by which Mcidas and GemC1 regulate ependymal cell generation we examined the expression of Foxj1 and c-Myb following deletion or overexpression of Mcidas and GemC1.…”
Section: Mcidas and Gemc1 Promote The Generation Of Ependymal Cells Tmentioning
confidence: 99%
“…It has been shown that Foxj1 and c-Myb regulate the differentiation of RGCs towards the ependymal cell lineage and maintain their identity (Jacquet et al, 2009;Malaterre et al, 2008), and that Six3 expression is crucial for the loss of radial glial characteristics of the differentiating ependymal cells (Lavado and Oliver, 2011). Ependymal cells contain in their apical surface multiple motile cilia and reside in a single cell layer facing the lateral ventricles (Doetsch et al, 1997), forming rosettelike structures surrounding a type B1 NSC (Mirzadeh et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, there are some indications that A-Myb and c-Myb may have a role in the mouse olfactory system. A-myb is expressed in the olfactory epithelium, while c-myb mutant mice have smaller olfactory bulbs (Trauth et al 1994;Malaterre et al 2008).…”
Section: Evolutionary Conservation and Odor Receptor Gene Expressionmentioning
confidence: 99%
“…Knockout mice have been generated for 7 of the 8 genes with neuronal enhancer activity, but a conditional brain-specific knockout has only been described for c-myb, which like Scl was found to be critical for neuronal development. 52 Known target genes of Scl in more mature erythroid and megakaryocyte cells such as Gata1, 53 Lmo2, 54 ␣-and ␤-globin, 20,55 as well as NF-E2 promoter, 56 respectively, were not bound by Scl in the HPC-7 cell line. We also did not observe binding to the Runx3 promoter, which previously showed low-level Scl binding in fetal liver and no binding in E8.5 yolk sac, 18 suggesting potential binding of Scl within subpopulations of hematopoietic progenitor cells.…”
mentioning
confidence: 94%